FUZZY MAMDANI FORECASTING OF BLOOD BAG SUPPLY AT INDONESIAN RED CROSS BLOOD IN DELI SERDANG REGENCY UNIT - Ika Silvia Ramadani; Rina Filia Sari; Hendra Cipta (INFOKUM, 2022)
An increase in population will cause an increase in the amount of processed blood reserves. Therefore, it is necessary to forecast the amount of production within a certain period of time to see the number of blood bags that may be needed in order to meet demand correctly and in the appropriate amount. The method used is Mamdani fuzzy with data sourced from the Indonesian Red Cross Blood Unit Deli Serdang Regency from January 2019 to January 2020. This study shows that the Mamdani District fuzzy method can be implemented for forecasting the production of blood bags in January and February 2020.